Zefran Textile Research Laboratory - Dow Chemical Company (1956)
General view of an unidentified employee examining a bobbin from a drawtwister used for the production of Zefran, an acrylic fiber, at the Dow Chemical Company's Textile Research Laboratory located in Pittsburg, California.
Keywords: Employees; Laboratories; Dow Chemical Company; Machinery; Acrylic fibers